Identification of disease-associate variants of aggressive periodontitis using genome-wide association studies - Chiharu Fujihara; Osa Amila Hafiyyah; Shinya Murakami (Japanese Dental Science Review, 2023)
Aggressive periodontitis (AgP), Stage III or IV and Grade C according to the new periodontitis classification, is characterized by the rapid destruction of periodontal tissues in the systemically healthy population and often causes premature tooth loss. The presence of familial aggregation suggests the involvement of genetic factors in the pathogenesis. However, the genes associated with the onset and progression of the disease and details of its pathogenesis have not yet been fully identified. In recent years, the genome-wide approach (GWAS), a comprehensive genome analysis method using bioinformatics, has been used to search for disease-related genes, and the results have been applied in genomic medicine for various diseases, such as cancer. In this review, we discuss GWAS in the context of AgP. First, we introduce the relationship between single-nucleotide polymorphisms (SNPs) and susceptibility to diseases and how GWAS is useful for searching disease-related SNPs. Furthermore, we summarize the recent findings of disease-related genes using GWAS on AgP inside and outside Japan and a possible mechanism of the pathogenesis of AgP based on available literature and our research findings. These findings will lead to advancements in the prevention, prognosis, and treatment of AgP.